Pengaruh Kurikulum Merdeka Belajar Terhadap Motivasi Belajar Siswa di SD Katolik 1 Bunda Hati Kudus Taratara - Dalia, Adrianus; Turang, Kevin; Mangelep, Valeri Brigita (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2024)
The curriculum is an important and main part of the world of education. The curriculum aims to regulate the running of the education process. The curriculum provides regularity in the implementation of the learning process. In Indonesia itself, the curriculum has undergone many changes. Curriculum changes aim to provide newness or improvement from the previous curriculum. Currently, Indonesia has replaced its curriculum with the name Merdeka Belajar Curriculum. The Merdeka Belajar Curriculum is a renewal or improvement from the previous curriculum, namely the 2013 Curriculum. The Merdeka Belajar Curriculum provides opportunities for students to learn more flexibly, with more and broader learning resources and media, so that it can arouse students' interest or motivation to learn. The method used in this study is the quantitative method. The results of the study show that the Merdeka Belajar Curriculum has an influence on Student Learning Motivation at SD Katolik 1 Bunda Hati Kudus Taratara